Democracy and the public space in Latin America - Avritzer, Leonardo (Princeton University Press, 2002)
This is a bold new study of the recent emergence of democracy in Latin America. Leonardo Avritzer shows that traditional theories of democratization fall short in explaining this phenomenon. Scholars have long held that the postwar stability of Western Europe reveals that restricted democracy, or "democratic elitism," is the only realistic way to guard against forces such as the mass mobilizations that toppled European democracies after World War I. Avritzer challenges this view. Drawing on the ideas of Jurgen Habermas, he argues that democracy can be far more inclusive and can rely on a sphere of autonomous association and argument by citizens. He makes this argument by showing that democratic collection action has opened up a new "public space" for popular participation in Latin American politics.